Black Hawk down - Nolan, Ken; Scalia, Pietro; Zimmer, Hans; Hartnett, Josh 1978-; McGregor, Ewan 1971-; Sizemore, Tom 1961-; Bana, Eric; Fichtner, William; Bremner, Ewen; Shepard, Sam 1943-; Bowden, Mark
With exacting detail, the film re-creates the American siege of the Somalian city of Mogadishu in October 1993, when a 45-minute mission turned into a 16-hour ordeal of bloody urban warfare. Helicopter-borne U.S. Rangers were assigned to capture key lieutenants of Somali warlord Muhammad Farrah Aidid, but when two Black Hawk choppers were felled by rocket-propelled grenades, the U.S. soldiers were forced to fend for themselves in the battle-torn streets of Mogadishu, attacked from all sides by armed Aidid supporters.